New materials on the Khitan small script : a critical edition of Xiao Dilu & Yelü Xiangwen - Wu, Yingzhe (Languages of Asia series, 2010)
This volume contains a state-of-the-art survey of Khitan Small Script studies, accompanied by a critical analysis of two recently discovered and previously unpublished epigraphic documents. The texts are reproduced in the original script, in transcription as well as in facsimile, and are supported by a preliminary translation, linguistic comments and index. This is the first ever critical edition of Khitan texts, and the two epigraphic documents analysed in the volume constitute a substantial addition to the extant corpus of Khitan Small Script materials.--Publisher's website.